2020
DOI: 10.1007/s40265-020-01335-7
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Systemic Treatments for Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a prevalent inflammatory skin condition that, depending on its severity, can cause enormous morbidity. Corticosteroids and systemic immunosuppression, traditionally standard of care for difficult-to-treat disease, have many undesirable side effects. The desire for targeted treatments along with an improved understanding of the pathophysiology of AD has spurred the development of novel treatments. In this article, we review promising new treatments and discuss how their targets-IL-13, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
79
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 46 publications
0
79
0
2
Order By: Relevance
“…However, chronic pruritus that lasts more than 6 weeks is highly problematic because it markedly deteriorates quality of life, mental health and sleep quality in the afflicted individuals [ 1 , 2 , 3 , 4 , 5 ]. Chronic pruritus is the major symptom in many inflammatory skin diseases such as atopic dermatitis, prurigo nodularis, eczema, chronic urticaria and psoriasis [ 1 , 2 , 3 , 4 ]. Scratching clearly exacerbates the predisposing dermatitis, which may further enhance pruritus and result in an itch/scratch vicious cycle [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chronic pruritus that lasts more than 6 weeks is highly problematic because it markedly deteriorates quality of life, mental health and sleep quality in the afflicted individuals [ 1 , 2 , 3 , 4 , 5 ]. Chronic pruritus is the major symptom in many inflammatory skin diseases such as atopic dermatitis, prurigo nodularis, eczema, chronic urticaria and psoriasis [ 1 , 2 , 3 , 4 ]. Scratching clearly exacerbates the predisposing dermatitis, which may further enhance pruritus and result in an itch/scratch vicious cycle [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed numerous itch-inducing factors or pruritogens [ 1 , 2 , 3 , 4 , 7 , 8 ]. Specific receptors for these pruritogens are expressed on cutaneous sensory nerve fibers, which are mostly small C-fibers innervating the epidermis and dermis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Topical therapy includes the application of corticosteroids, antihistamine, and immunosuppressants (e.g., calcineurin inhibitors and phosphodiesterase inhibitors) [ 5 ]. Systemic administration comprises immunosuppressant-modulators (e.g., cyclosporine), anti-metabolites (e.g., methotrexate and azathioprine), cytokine signaling inhibitor (e.g., JAK kinase inhibitor), antibiotics, and biological agents (e.g., targeted monoclonal antibodies) [ 6 , 7 , 8 , 9 ]. Topical steroids and immunosuppressants have been used as the primary agents; however, their value is limited by local side effects and insufficient efficacy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the new treatment options with antibodies (Ab), especially with the Ab Dupilumab, against interleukin-4 receptor revealed great potential without serious side effects [ 35 , 36 , 37 , 38 ]…”
Section: Introductionmentioning
confidence: 99%